Smoking prevalence and patterns among resident doctors at Aleppo University Hospital, Syria: a cross-sectional study - Mohamad moafak Hariri; Mohammed Moutaz Alshaghel; Mohamad Aref Dabbas; Muawia Alhasan; Mohamad Yazan Hamwi; Asaad Nazmi Alrefai; Alaa Kourdy; Mohamed Naji Sajee; Ahmad Kadan; Abdullah Khoury (Discover Public Health)
Abstract Background Smoking is a major public health concern globally. This study aimed to assess the prevalence and patterns of smoking among resident doctors at Aleppo university Hospital Syria, and explore influencing factors. Methods A cross sectional study recruited 294 resident doctors via self-administered questionnaire between October 2023 and January 2024. The questionnaire assessed smoking habits, demographics, and factors potentially associated with smoking. Data were analyzed respectively and with odds ratios. Results The smoking prevalence was 22.1% with water pipe use being most common (72.3%), followed by cigarettes (49.2%) and electronic cigarettes (15.4%). Male doctors were significantly more likely to smoke than females (39.5% vs. 10.3%). Smoking prevalence was associated with surgical specialty, higher stress levels, longer work hours, and lower personal satisfaction. A significant proportion of non-smokers (41.5%) reported exposure to secondhand smoke, primarily at home (63.2%). Conclusion This study identified a concerning smoking prevalence among resident doctors in Syria, with water pipe being the preferred method/type of tobacco use. Multifaceted interventions are needed to address smoking behaviours, including stress management techniques and limitations on secondhand smoke exposure. By targeting smoking among role models, this study contributes to the broader tobacco control efforts in Syria.